2011
DOI: 10.1007/s11182-011-9507-5
|View full text |Cite
|
Sign up to set email alerts
|

Artificial metamaterials and radio tomography

Abstract: 538.56Results of theoretical and experimental investigations of artificial metamaterials based on composite of straight and circular conductors for radio wave range are presented. It is demonstrated that for small conductor sizes, nonresonant character of metamaterial properties of the artificial medium is retained. The possibility of application of metamaterials for increasing resolution in radio tomography is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…On the basis of numerical model operations on interaction of an electromagnetic radiation with structure from elemental annuluses [2,3], the experimental model of metamaterial is created. The exemplar was executed in the form of matrix structure from the ring conductors located in frothed polystyrene.…”
Section: Experimental Studymentioning
confidence: 99%
“…On the basis of numerical model operations on interaction of an electromagnetic radiation with structure from elemental annuluses [2,3], the experimental model of metamaterial is created. The exemplar was executed in the form of matrix structure from the ring conductors located in frothed polystyrene.…”
Section: Experimental Studymentioning
confidence: 99%
“…Previously, the authors of this work presented the possibility of metamaterial creation for the radio range as an artificial composite medium made up of a certain oriented linear and circular conductors [3,4]. Such a medium may have a negative refractive index.…”
Section: Intorductionmentioning
confidence: 99%
“…Veselago predicted the unique properties of materials with a negative real part of the permittivity and permeability [1]. Later, a special interest was aroused by the works of D. Pendry of the possibility of developing "superlenses" allowing overcoming the diffraction limit [2].Previously, the authors of this work presented the possibility of metamaterial creation for the radio range as an artificial composite medium made up of a certain oriented linear and circular conductors [3,4]. Such a medium may have a negative refractive index.…”
mentioning
confidence: 99%
“…In the previous publications [4,5] authors showed a possibility of creation of metamaterials from the selfcontained ring conductors focused definitely, placed in polystyrene foam. Creation of such structures processes the long-lived and laborious.…”
Section: Introductionmentioning
confidence: 99%